Custom Procedure Packs - The Regina Experience - Boyd, Darlene (Operating Room Nurses Association of Canada Journal, 2004)
A custom procedure pack is a pre-packed bundle containing disposable drapes, gowns, and other items such as suctions, cauteries etc.